Оценка быстродействия помехоустойчивого счетчика Фибоначчи в минимальных кодах - Борисенко, А. А.; Маценко, С. М.; Гриненко, В. В.; Бережная, О. В.; Дегтяр, С. А. (НТУ "ХПИ", 2015)
В данной работе произведена оценка быстродействия фибоначчиевого счетчика импульсов, работающего в минимальных кодах Фибоначчи, получены для него соответствующие выражения. Быстродействие счетчика Фибоначчи определяется максимальным временем переходных процессов между двумя соседними состояниями счетчика, обратная величина к которому задает максимальную допустимую тактовую частоту счетчика. Однако оценка быстродействия такого счетчика Фибоначчи до сих пор не была произведена. Поэтому в данной работе ставится задача такой оценки.

In this paper we evaluated the performance of the Fibonacci pulse counter running in minimal Fibonacci codes, obtained the corresponding expression. There is no transfers in the counter and it enhance its performance compared with other types of counters, which have transfers and more complex structure. Furthermore, in this counter homogeneous structure is observed, which Fibonacci counters requiring back additional circuitry to implement the transition from the minimum to the maximum mold form and vice versa. Speed of the Fibonacci counter is determined by the maximum time of transients between the two neighboring states of the counter, the return of value which specifies the maximum allowable clock frequency of the counter. However, the evaluation of the performance of such Fibonacci counter still was not done. Therefore, in this paper, the task of such estimates. The shown estimates imply that with increase in the number of bits of the Fibonacci counter signal delay in it increases that can be attributed to a lack of the counter structure. However, the absence of transfers in the counter compensates to some extent for this deficiency. Performance of this counter also will be higher relative to the Fibonacci counters constructed on scan and convolution circuits, as such circuits are absent in this counter. Novelty and relevance of the proposed in the article approach to solving this problem is to find the corresponding expressions for assessing Fibonacci counter largest time delay of signals in logic circuits of the device.
Performance evaluation of noise immunity Fibonacci counter in minimally codes
Keywords: аппаратурные затраты; импульс; частота; Fibonacci numbers; Fibonacci counter; hardware resources; performance; error detection